Description of Cathorops mapale, a new species of sea catfish (Siluriformes: Ariidae) from the Colombian Caribbean, based on morphological and mitochondrial evidence - Betancur-R., Ricardo; P., Rturo Acero (Zootaxa, 2005)
A new species of sea catfish (Ariidae), Cathorops mapale, is described from the central and southwestern Colombian Caribbean coast. The species is distinguished from other Cathorops species from the western Atlantic by the following combination of features: 20–24 anterior gill rakers on first gill arch, 18–21 anterior gill rakers on second gill arch; maxillary barbels 27.8–39.3% standard length; medial head groove long and deep, extending posteriorly almost to supraoccipital keel. This species has been widely misidentified as C. spixii (Agassiz), a species known from Brazil to the Guianas. Based on mitochondrial evidence (cytochrome b and ATP synthase 8/6), C. mapale is more closely related to the eastern Pacific C. fuerthii (Steindachner) species group (2.2–2.8% sequence divergence) than to the C. spixii clade (5.9–6.2% sequence divergence). C. mapale is distinguished from the C. fuerthii group by having higher anterior gill raker counts on the first (14–15 in the C. fuerthii group) and second (15–17 in the C. fuerthii group) gill arches, and by having a smaller mouth (8.3–10.6% standard length in C. mapale and 11.0–11.6% standard length in the C. fuerthii group).